2006
DOI: 10.1353/sls.2006.0019
|View full text |Cite
|
Sign up to set email alerts
|

How Many People Use ASL in the United States? Why Estimates Need Updating

Abstract: This article traces the sources of the estimates of the number of American Sign Language users in the United States. A variety of claims can be found in the literature and on the Internet, some of which have been shown to be unfounded but continue to be cited. In our search for the sources of the various (mis)understandings, we have found that all of the data-based estimates of the number of people who use ASL in the United States have their origin in a single study published in the early 1970s, which inquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(99 citation statements)
references
References 30 publications
0
94
0
1
Order By: Relevance
“…The ASL stories in the spatial reference study were a subset of those shown to participants in the larger study. In the larger study, animations appeared in two versions: (1) some with spatial reference points and pointing pronouns (some of these animations contained contrastive role shift and some did not) and (2) animations in which the signer does not use any spatial reference points or pointing pronouns. In the spatial reference study (presented in this article), all of the space animations contained use of contrastive role shift.…”
Section: Participants and Design Of The Spatial Reference Studymentioning
confidence: 99%
“…The ASL stories in the spatial reference study were a subset of those shown to participants in the larger study. In the larger study, animations appeared in two versions: (1) some with spatial reference points and pointing pronouns (some of these animations contained contrastive role shift and some did not) and (2) animations in which the signer does not use any spatial reference points or pointing pronouns. In the spatial reference study (presented in this article), all of the space animations contained use of contrastive role shift.…”
Section: Participants and Design Of The Spatial Reference Studymentioning
confidence: 99%
“…ASL is not just a manual presentation of an English sentence; it has its own word-order, syntactic constructions, and vocabulary of signs (which may not have one-to-one equivalence with English words). ASL is used as a primary means of communication for about one half million people in the United States [15]. Because of the differences between English and ASL, it is possible to have ASL fluency yet significant difficulty reading English.…”
Section: Motivations and Related Workmentioning
confidence: 99%
“…(U.S. 4 th -grade students are typically age 10.) There are over 500,000 people in the U.S. who use American Sign Language (ASL) as a primary language [22]. Given the linguistic differences between English and American Sign Language (ASL), it is possible to be fluent in one language but not the other.…”
Section: Introductionmentioning
confidence: 99%